Improving urban mining practices for optimal recovery of resources from e-waste. (September 2017) - Tesfaye, Fiseha; Lindberg, Daniel; Hamuyuni, Joseph; Taskinen, Pekka; Hupa, Leena
Highlights: State-of-the-art e-waste recycling technologies and strategies have been evaluated. Deficiencies in the e-waste recycling chain are highlighted. Mechanisms to increase collection rate of End-of-Life devices are presented. Feasible options for e-waste recycling process routes are described. Alternatives for optimal recovery of resources from e-waste are discussed. Abstract: In this article, current progress in urban mining related to e-waste recycling is reviewed and associated state-of-the-art recycling technologies are evaluated. As sufficient volume of e-waste is a limiting factor for its recycling economy, the need for the establishment of effective e-waste collection mechanisms, particularly for small sized End-of-Life (EoL) devices, is emphasized in terms of the need for effective government policies, increased public awareness, economic incentives, establishing industry-funded co-regulatory agreements, etc. Feasible options for e-waste recycling through pyro- and hydro-metallurgical process routes are reviewed. Deficiencies in e-waste recycling chains are highlighted, and recommendations to improve the current very low collection rate of small sized EoL devices such as mobile phones are made. Optimization of the recovery of the critical metals and energy through different processing options is discussed.